The Order of Operations
The Order of Operations Consider the expression, 2 + 5 x 4
The Order of Operations Consider the expression, 2 + 5 x 4 Evaluate the expression by doing the multiplication first.
The Order of Operations Consider the expression, 2 + 5 x 4 Evaluate the expression by doing the multiplication first. 2 + 5 x 4 = 2 + 20 = 22
The Order of Operations Consider the expression, 2 + 5 x 4 Evaluate the expression by doing the multiplication first. 2 + 5 x 4 = 2 + 20 = 22 Evaluate the expression by doing the addition first.
The Order of Operations Consider the expression, 2 + 5 x 4 Evaluate the expression by doing the multiplication first. 2 + 5 x 4 = 2 + 20 = 22 Evaluate the expression by doing the addition first. = 7 x 4 = 28
The Order of Operations Consider the expression, 2 + 5 x 4 Evaluate the expression by doing the multiplication first. 2 + 5 x 4 = 2 + 20 = 22 Evaluate the expression by doing the addition first. = 7 x 4 = 28 We need rules!
The Order of Operations BEDMAS
The Order of Operations BEDMAS B E DM AS
The Order of Operations BEDMAS B - Do operations in brackets first. E DM AS
The Order of Operations BEDMAS B - Do operations in brackets first. E - Evaluate exponents next. DM AS
The Order of Operations BEDMAS B - Do operations in brackets first. E - Evaluate exponents next. DM - Do dividing and multiplying in the order they appear. AS
The Order of Operations BEDMAS B - Do operations in brackets first. E - Evaluate exponents next. DM - Do dividing and multiplying in the order they appear. AS - Do adding and subtracting in the order they appear.
The Order of Operations BEDMAS Ex) (-3) x (-5) + (+18) ÷ (-3)
The Order of Operations BEDMAS Ex) (-3) x (-5) + (+18) ÷ (-3) = (+15) + (-6)
The Order of Operations BEDMAS Ex) (-3) x (-5) + (+18) ÷ (-3) = (+15) + (-6) = (+9)
The Order of Operations BEDMAS Ex) [(-8) – 15] x (-2)
The Order of Operations BEDMAS Ex) [(-8) – 15] x (-2) = [(-8) + (-15)] x (-2)
The Order of Operations BEDMAS Ex) [(-8) – 15] x (-2) = [(-8) + (-15)] x (-2) = (-23) x (-2)
The Order of Operations BEDMAS Ex) [(-8) – 15] x (-2) = [(-8) + (-15)] x (-2) = (-23) x (-2) = (+46)
The Order of Operations BEDMAS Ex) [(+4) + (-3)2 – 23]2
The Order of Operations BEDMAS Ex) [(+4) + (-3)2 – 23]2 = [(+4) + (-3) x (-3) – 2 x 2 x 2]2
The Order of Operations BEDMAS Ex) [(+4) + (-3)2 – 23]2 = [(+4) + (-3) x (-3) – 2 x 2 x 2]2 = [(+4) + 9 – 8]2
The Order of Operations BEDMAS Ex) [(+4) + (-3)2 – 23]2 = [(+4) + (-3) x (-3) – 2 x 2 x 2]2 = [(+4) + 9 – 8]2 = 52
The Order of Operations BEDMAS Ex) [(+4) + (-3)2 – 23]2 = [(+4) + (-3) x (-3) – 2 x 2 x 2]2 = [(+4) + 9 – 8]2 = 52 = 25
The Order of Operations Ex) (-4)2 + (-2)(-3) 7 + (-9)
The Order of Operations Ex) (-4)2 + (-2)(-3) 7 + (-9) = 16 + 6 -2
The Order of Operations Ex) (-4)2 + (-2)(-3) 7 + (-9) = 16 + 6 -2 = 22
The Order of Operations Ex) (-4)2 + (-2)(-3) 7 + (-9) = 16 + 6 -2 = 22 = -11
The Order of Operations Ex) (-4)2 + (-2)(-3) 7 + (-9) = 16 + 6 -2 = 22 The numerator and denominator must be -2 evaluated before dividing. = -11
The Order of Operations Ex) (-4)2 + (-2)(-3) 7 + (-9) = 16 + 6 -2 = 22 The numerator and denominator must be -2 evaluated before dividing. = -11 It’s as if they were in brackets.
The Order of Operations Is there a difference between the following? (-3)4 and -34 = (-3)(-3)(-3)(-3) = (+9)(-3)(-3) = (-27)(-3) = (+81) -34 = -(34) = -(3 x 3 x 3 x 3) = - 81 Yes there is a difference. Ask, “What is the base of the power?”
The Order of Operations Evaluate the following expression when x = 3 and y = -2 4x2 – (5 + y3) = 4(3)2 – (5 + (-2)3) = 4(9) – (5 + (-8)) = 36 – (-3) = 36 + (+3) = 39 jjjjjjjj